Spectacularization of overseas work in Filipino commercial films - Tan, Katrina Ross A. (2017)
In the years following the institutionalization of overseas work in 1974 until today, a number of commercial films on overseas work have been produced and starred in by the movie industry's biggest names. Commercial cinema in the Philippines has always banked on the popularity of movie stars to sell the film; however, these stars also carry with them the power to glamorize their roles, thus maintaining the spectacle of the cinema.
This study analyzed Caregiver, a commercial film released in 2008 starring one of the biggest movie stars, Sharon Cuneta, playing the role of an Overseas Filipino Worker. The analysis examined the film by its use of star power to affect the filmic discourse on overseas work. This article discusses how the film's use of a major film star, including its publicity and marketing campaigns, and film reviews it received ultimately resulted in the spectacularization of overseas work in commercial films.
The study asserts that this spectacularization contributes to naturalizing a discourse on overseas work, a discourse propagated by the government in its aggressive campaign to condition the audience on how they view and respond to the lure of overseas work. This demonstrates the complicity of commercial media to the State's labor export orientation that ultimately benefits both.
Keywords: Overseas Filipino Workers Film; Women caregivers